Molecular structure of two C-aryl-iminocyclitols studied by X-ray and ab initio calculations - Zukerman-Schpector, Julio (2005)
(1), C18H26N2O7, Mr = 382.41, P212121, a = 9.7215(9), b = 10.687(1), c = 18.399(2) Å, V = 1911.6(3) Å3, Z = 4, R1 = 0.0395. (2), C12H18ClNO4, Mr = 275.72, P21, a = 10.431(1), b = 6.9223(8), c = 18.043(2) Å, β = 102.085(7)°, V = 1273.9(2) Å3, Z = 4, R1 = 0.0578. The five membered ring is in a twist conformation in (1) and in the two independent molecules of (2) in an envelope conformation. In both compounds the hydroxyl moieties are involved in hydrogen bonds. The compounds were studied by HF/6-31G** computations. © by Oldenbourg Wissenschaftsverlag, München.